2020
DOI: 10.1103/physrevd.102.034515
|View full text |Cite
|
Sign up to set email alerts
|

Application of dilaton chiral perturbation theory to Nf=8 , SU(3) spectral data

Abstract: We extend dilaton chiral perturbation theory (dChPT) to include the taste splittings in the Nambu-Goldstone sector observed in lattice simulations of near-conformal theories with staggered fermions. We then apply dChPT to a recent simulation by the LSD Collaboration of the SU(3) gauge theory with 8 fermions in the fundamental representation, which is believed to exhibit near-conformal behavior in the infrared, and in which a light singlet scalar state, nearly degenerate with the pions, has been found. We find … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…1, 5 and 6. The values we get lie close to the allowed ranges found in earlier dilaton studies of the N f = 8 theory [33,58] which reported good agreement between the tree level EFT and the available lattice data, but did not consider scattering observables. The estimated uncertainties of the fit parameters are obtained by calculating the inverse Hessian of the chi-squared function at its minimum, to extract the standard errors.…”
Section: B Comparison With Lattice Datasupporting
confidence: 87%
“…1, 5 and 6. The values we get lie close to the allowed ranges found in earlier dilaton studies of the N f = 8 theory [33,58] which reported good agreement between the tree level EFT and the available lattice data, but did not consider scattering observables. The estimated uncertainties of the fit parameters are obtained by calculating the inverse Hessian of the chi-squared function at its minimum, to extract the standard errors.…”
Section: B Comparison With Lattice Datasupporting
confidence: 87%
“…Here we review some of the fits performed in Ref. [11] of the tree-level predictions to data for the pion mass and decay constant, as well as the dilaton mass, as a function of the fermion mass. 1 The ensembles of Ref.…”
Section: Fits To Lsd Data [1 2]mentioning
confidence: 99%
“…2 we show results of one of the fits of Ref. [11], using data for M 2 ⇡ /F 2 ⇡ , aF ⇡ and M 2 ⌧ /F 2 ⇡ at the lowest four am values. The fit has a p-value of 0.89.…”
Section: Fits To Lsd Data [1 2]mentioning
confidence: 99%
“…We emphasise that at T = 0, it is very hard to distinguish a chirally broken theory from a mass-deformed conformal theory, see, for instance, Refs. [76][77][78].…”
Section: Large N Fmentioning
confidence: 99%